Identificación de staphylococcus pseudintermedius y gen de resistencia meca por medio de pcr de 86 hisopados corneales obtenidos de perros sanos de la ciudad de Riobamba. - Asqui Aguayo, Santiago Alejandro (Machala : Universidad Técnica de Machala, 2024)
"The therapeutic management of ocular pathologies is based on the timely use of antibiotics to prevent irreversible effects that harms the ocular globe. Currently, It has been identified to S. pseudintermedius as an opportunistic bacterium that prevails in the normal microbiome of healthy dogs´conjunctiva and cornea. As a result of which poses a threat to the effective treatment of eye infections due to the evolutionary capacity of its strains, which acquires genetic characteristics of antimicrobial resistance. The identification of the mecA resistance gene in S. pseudintermedius allows understanding the existence of methicillin-resistant populations in healthy dogs, and developing strategies for the responsible use of antibiotics. The objective of this research was to identify these bacteria, through the sequencing of the spsJ gene in S. pseudintermedius and the mecA resistance gene, using the Nested PCR technique. Samples were obtained from 86 corneal swabs in healthy dogs from Riobamba city. Moreover, the study focused on determining whether there is a relation between the lacrimal production and the skull shape with the presence of the bacterium. For the data analysis, frequencies and associations were described by using Chi-square test. Thirthy-three percent of the samples were determined to be S. pseudointermedius, and five percent of the total samples have the mecA resistance gene. It did not determine an associative effect due to lacrimal production, age, sex or reproductive status, although there was some evidence that exists a greater likelihood of finding these bacteria in brachycephalic animals. These data become significant for timely medical decision-making in ocular pathologies and contribute to prevent infections as well as to enrich the global and local database on bacterial resistance. This is one of the first study took place in Ecuador and the first one done in canine ocular microbiome."
"El manejo terapéutico de patologías oculares se basa en el uso oportuno de antibióticos, para evitar efectos irreversibles que perjudique al globo ocular. Actualmente, se ha identificado a S. pseudintermedius como la bacteria oportunista más prevalente en el microbioma normal de la conjuntiva y córnea de perros sanos. Por lo que representa una amenaza para el tratamiento efectivo de infecciones oculares, debido a la capacidad evolutiva de sus cepas, que adquieren características genéticas de resistencia antimicrobiana. La identificación del gen de resistencia mecA de S. pseudintermedius permite comprender la existencia de poblaciones resistentes a meticilina en caninos sanos y generar estrategias para el uso responsable de antibióticos. El objetivo de esta investigación fue identificar a estas bacterias mediante la secuenciación del gen spsJ para S. pseudintermedius y gen de resistencia mecA por técnica de PCR Nested en muestras obtenidas de 86 hisopados corneales de perros sanos de la ciudad de Riobamba. Además, se investigó si existe relación entre la producción lacrimal y la conformación del cráneo, con presencia de la bacteria. Para el análisis de datos se describieron frecuencias y asociaciones mediante pruebas de Chi2. Se determinó que el 33% de las muestras fueron S. pseudointermedius, y el 5% del total de muestras tiene el gen de resistencia mecA. No se determinó un efecto asociativo con la producción lagrimal, edad, sexo o estado reproductivo, aunque se hallaron indicios de una mayor probabilidad de hallazgo de esta bacteria en animales braquiocefálicos. Estos datos se tornan relevantes en la toma decisiones médicas oportunas en patologías oculares y sirven para prevenir infecciones, aporta a la base de datos mundial y local sobre resistencia microbiana. Este trabajo corresponde a los primeros estudios realizados en el Ecuador y el primero en el microbioma ocular canino.
Keywords: MICROBIOMA CORNEAL; RESISTENCIA BACTERIANA; BRAQUIOCEFÁLICO; PCR NESTED